2005
DOI: 10.1158/1535-7163.mct-05-0047
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant neuroblastoma cells are responsive to arsenic trioxide at both normoxia and hypoxia

Abstract: Despite intensive treatment, the outcome of high-risk neuroblastoma patients is poor with acquired multidrug resistance as an important cause. Previously, our group has shown that arsenic trioxide (As 2 O 3 ) kills multidrugresistant neuroblastoma cells in vitro and in vivo at clinically tolerable doses. Regions of tissue hypoxia often arise in aggressive solid tumors, and hypoxic tumors exhibit augmented invasiveness and metastatic ability in several malignancies. Furthermore, hypoxia may impair the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
(42 reference statements)
2
9
0
Order By: Relevance
“…Our findings that pancaspase inhibition does not block arsenic trioxide-induced cell death or Bax cleavage and that the fraction of cytoplasmic vs mitochondrial cytochrome c in arsenic trioxide-treated neuroblastoma cells is small, further support a non-mitochondrial p18 Bax dependent death route (Karlsson et al, 2004). We also show that in conformity with arsenic trioxide treatment in normoxia, proteolytic activation of the proapoptotic protein Bax takes place when hypoxic neuroblastoma cells are treated with arsenic trioxide (Karlsson et al, 2005). Bax cleavage is not as pronounced, however, and it is possible that other cell death mechanisms are activated as a complement under hypoxic conditions.…”
Section: Cellssupporting
confidence: 60%
See 2 more Smart Citations
“…Our findings that pancaspase inhibition does not block arsenic trioxide-induced cell death or Bax cleavage and that the fraction of cytoplasmic vs mitochondrial cytochrome c in arsenic trioxide-treated neuroblastoma cells is small, further support a non-mitochondrial p18 Bax dependent death route (Karlsson et al, 2004). We also show that in conformity with arsenic trioxide treatment in normoxia, proteolytic activation of the proapoptotic protein Bax takes place when hypoxic neuroblastoma cells are treated with arsenic trioxide (Karlsson et al, 2005). Bax cleavage is not as pronounced, however, and it is possible that other cell death mechanisms are activated as a complement under hypoxic conditions.…”
Section: Cellssupporting
confidence: 60%
“…We therefore investigated whether a low oxygen level (1% O 2 ) results in deteriorated cytotoxic effects of arsenic trioxide in different neuroblastoma cells. Our data show that the cytotoxic effect is retained under hypoxic conditions, even in multidrug-resistant neuroblastoma cells such as SK-N-BE(2)c and SK-N-FI (Karlsson et al, 2005). Despite that the neuroblastoma cells subjected to hypoxia is dividing somewhat more slowly, the cytotoxic effect of arsenic trioxide is maintained.…”
Section: Neuroblastoma Cellsmentioning
confidence: 69%
See 1 more Smart Citation
“…At clinically tolerable concentrations, As 2 O 3 also induces cell death in multidrug-resistant neuroblastoma cells in vitro and in vivo (9,10). The cytotoxic effect of As 2 O 3 is retained in neuroblastoma cells at hypoxia (11), a property of potential clinical importance because hypoxic areas are frequent in solid tumors and have been linked to drug-resistant phenotypes (12).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore of great significance to investigate novel chemotherapeutic drugs that are effective to kill tumour cells at hypoxia. Some studies showed that the cytotoxic effect of arsenic trioxide (As 2 O 3 ) on malignant cells was not reduced at hypoxia (Kalsson et al, 2005;Yan et al, 2005). As 2 O 3 , a potent anticancer agent, has been used for decades by Chinese investigators to treat acute promyelocytic leukemia (APL) patients.…”
Section: Introductionmentioning
confidence: 99%